Ursolic acid and rosmarinic acid ameliorate alterations in hippocampal neurogenesis and social memory induced by amyloid beta in mouse model of Alzheimer’s disease - Mirza, Fatima Javed; Zahid, Saadia (Frontiers in Pharmacology, 2022)
Alzheimer’s disease (AD) is a multifaceted neurodegenerative disorder characterized by substantial neuronal damage which manifests in the form of deficits in memory and cognition. In spite of the debilitating nature of AD, a dearth of treatment strategies calls for the need to develop therapeutic agents that stimulate neurogenesis and alleviate the associated cognitive deficits. The present study investigates the therapeutic potential of two major phytochemicals, rosmarinic acid (RA) and ursolic acid (UA) in an amyloid beta1-42 (Aβ1-42)-induced model of AD. UA, a natural pentacyclic triterpenoid and RA, a phenolic ester are major bioactive constituents of Rosmarinus officinalis, which is a medicinal herb belonging to family Lamiaceae and exhibiting significant biological properties including neuroprotection. Donepezil, a second generation cholinesterase inhibitor approved for the treatment of mild, moderate and severe AD is used as control. Out of eight groups of male BALB/c mice, stereotaxic surgery was performed on four groups (n= 6 each) to introduce Aβ1-42 in the hippocampus followed by treatment with vehicle (phosphate-buffered saline (PBS)), donepezil, UA or RA. The other four groups were given vehicle, donepezil, UA and RA only. Behavior analysis for social interaction was performed which constitutes the social affiliation and the social novelty preference test. Presence of Aβ plaques and expression of neurogenesis markers i.e., doublecortin (DCX) and Ki-67 were also assessed. Results revealed the neuroprotective effect of UA and RA observed through substantial reduction in Aβ plaques as compared to the Aβ1-42- and donepezil-treated groups. The neuronal density was also restored as evident via DCX and Ki-67 immunoreactivity in Aβ1-42+RA and Aβ1-42+UA-treated groups in comparison to Aβ1-42-treated and Aβ1-42+donepezil-treated groups. The social affiliation was reestablished in the Aβ1-42 administered groups treated with UA and RA. Molecular docking studies further validated the comparable binding of UA and RA with Ki-67 and DCX to that of donepezil. Our findings suggest that UA and RA are potential neuroprotective compounds that reverses the histological hallmarks of AD and ameliorate impaired social memory and hippocampal neurogenesis.